The best of leaders at the worst of times: medical scientist and war premier. (August 2020) - Coni, Nicholas
Professor Juan Negrín López was Prime Minister of the democratically elected left-wing government of Spain for the latter two-and-a-half years of the three-year Civil War which ravaged the country between 1936 and 1939. The side loyal to the government lost, partly because of the generous aid received by their opponents from Germany and Italy, partly because of the Anglo-French agreement, observed by most countries but ignored by Germany and Italy, to outlaw arms supplies to either side, partly because of internal dissent, and partly because of the greater military capability of the enemy. Negrín led the country with tenacity and wisdom, but is remembered with ambivalence in Spain, and hardly at all elsewhere, although he spent the years of his post-war exile in the UK and France. This paper draws attention to a member of the medical profession who achieved both academic and political distinction, but whose career ended in a disaster which he was powerless to prevent. Among his admirable qualities, he should be remembered for his courage. Like most wars, the Spanish Civil War had its share of psychopaths and villains – but also its share of heroes, and Juan Negrín belongs among their number.